E-governance for good governance the national e-governance action Plan - Kaushiva, Anamika (2005)
Good governance is an act of balancing the interests that cut across community, space and time. The task is multi-dimensional and requires the employment of tools that can articulate the process through meaningful participation of the common man. The article emphasises that the challenge before the country is to usher in changes which can foster a meaningful relationship between state, market and society. - Reproduced.
Keywords: Public administration; Good governance; Electronic governance